Innovative UV sensor based on highly birefringent fiber covered by graphene oxide - Lesiak, Piotr; Sobotka, Piotr; Bieda, Marcin; Dużyńska, Anna; Wróblewska, Anna; Chychłowski, Miłosz; Woliński, Tomasz (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> The innovative idea of this paper implies the possibility to exploit the properties of graphene oxide (GO) to UV radiation sensor design. The idea assumes that a temperature change around the fiber can be induced by UV radiation. Particular attention in the case of UV radiation detection merits of GO, which has a high UV absorption only. UV lighting will increase the internal energy of the GO and consequently locally raise the temperature on the surface of the optical fiber. The temperature is changing stress distribution in the fiber. Full Text: PDF References O. Lupan et al., "Ultraviolet photoconductive sensor based on single ZnO nanowire", Phys. Stat. Sol. (a) 207(7), 1735 (2010). CrossRef G. Suchaneck, G. Gerlach, "Ferroelectric–Semiconductor UV Sensors", Phys. Stat. Sol. (a) 185(1), 115 (2001). CrossRef K.T.V. Grattan, T. Sun, "Fiber optic sensor technology: an overview", Sensors and Actuators A: Physical 82, 40 (2000). CrossRef C. Fitzpatrick et al., "A novel multi-point ultraviolet optical fibre sensor based on cladding luminescence", Meas. Sci. Technol. 14(8), 1477 (2003). CrossRef A.V. Joža et al., "Simple and Low-cost Fiber-optic Sensors for Detection of UV Radiation", Telfor Journal 4(2), 133 (2012). DirectLink P. Lesiak et al., Acta Phys. Polon. A 120(4), 698 (2011). DirectLink M. Segal, "Selling graphene by the ton", Nature Nanotechnology 4, 612 (2009). CrossRef T.R. Wolinski, "Polarimetric Optical Fibers and Sensors" in Progress in Optics, ed. Emil Wolf (North Holland, Amsterdam, vol. XL, pp. 1-75, 2000). T.R. Wolinski, "Polarization Phenomena in Optical Systems’, in Enc. Opt. Engineering, ed. R. Diggers (M. Dekker, New York, pp. 2150-2175, 2003). W.J. Bock, A.W. Domanski, T.R. Wolinski, "Influence of high hydrostatic pressure on beat length in highly birefringent single-mode bow tie fibers", Appl. Opt. 29, 3484 (1990). CrossRef Z.C. Wu et al., "Transparent, Conductive Carbon Nanotube Films", Science 305, 1273 (2004). CrossRef A. Jorio, M. Dresselhaus, R. Saito, G.F. Dresselhaus, Raman Spectroscopy in Graphene Related Systems (Wiley-VCH, 2011). CrossRef G. Sobon, J. Sotor, J. Jagiello, R. Kozinski, M. Zdrojek, M. Holdynski, P. Paletko, J. Boguslawski, L. Lipinska, K.M. Abramski, "Graphene Oxide vs. Reduced Graphene Oxide as saturable absorbers for Er-doped passively mode-locked fiber laser", Opt. Expr. 20, 19463 (2012) CrossRef F. Zhang, J.W.Y. Lit, "Temperature and strain sensitivity measurements of high-birefringent polarization-maintaining fibers", Appl. Opt. 32(13), 2213 (1993). CrossRef S. Pei, H.M. Cheng, "The reduction of graphene oxide", Carbon 50, 3210 (2012). CrossRef